An Efficient Micropropagation Protocol and Optimization of Phytohormones for Gladiolus Species for Commercial Cultivation (Plant Tissue Culture and Biotechnology, 2026)
Conventional propagation of Gladiolus through corms and cormels is slow, season-dependent, and insufficient to meet the increasing demand for quality planting materials, highlighting the need for an efficient micropropagation system for commercial uses. This study aimed to develop a reproducible in vitro protocol and optimization of various concentration of phytohormones using five Gladiolus spp. Healthy cormel explants of five gladiolus varieties, e.g. (add names of the five varieties) were cultured on Murashige and Skoog medium supplemented with different concentrations of 6-benzylaminopurine (BAP). Significant variation was observed among treatments and varieties for shoot proliferation, shoot length, and leaf number. The highest shoot multiplication (4.80 shoots explant-1), shoot length (6.45 cm), and leaf number (5.28 leaves explant-1) were obtained on MS medium with 2.0 mg/l BAP. Among the varieties, Red Sindoor showed better performance, producing up to 5.60 shoots explant-1 under the same treatment. Rooting was most effective on MS medium supplemented with 1.5 mg/l indole-3-butyric acid (IBA), where Red Sindoor also exhibited the highest rooting percentage (94.5%), root number (6.0), and root length (6.35 cm). The regenerated plantlets were successfully acclimatized and recorded the survival rates from 78.0% to 90.0%. These findings indicated that 2.0 mg/l BAP and 1.5 mg/l IBA were optimal for shoot multiplication and rooting, respectively. The developed protocol offers a practical and scalable approach for rapid production of disease-free, genetically uniform planting materials, contributing to the advancement of commercial application in floriculture.Plant Tissue Cult. & Biotech. 36(1): 67-78, 2026 (June)